A Framework For Detecting Bluetooth Mobile Worms. - Sarwar, Usman; Ramadass, Sureswaran; Budiarto, Rahmat (2007)
Bluetooth is an industrial standard for wireless specification for wireless personal area network (PAN). In recent years, Bluetooth technology has become a standard in mobile devices such as cell phones, smart phones and personal digital assistant (PDA) for short range communication.